Contribution of generator-load pairs in distribution networks power losses - Mirko Todorovski and Dragoslav Rajičić (Elsevier, 2020)
The focus of the research presented here is developing a method to calculate contribution of each generator-load pair in total distribution network power losses. To do this we calculate current component from any generator to any load and then multiply each of these conjugate current components by difference between corresponding generator node voltage and load node voltage. This way there are no quadratic expressions and problems with non-separability of losses. Also, the procedure breaks down the losses in such a way that one may investigate how each power transaction contributes to the losses. The idea to create such kind of method is to assist network users (producers and consumers) obtaining detailed information about distribution of power losses among network branches, and base on this information to consider corresponding transparent and non-discriminatory actions. Developing the method, no problematic assumptions or simplifications were used. Hence, the method is exact and do not consider privilege to any network user. In addition, it handles PV nodes without additional inconveniencies. Accordingly comparing this method with methods allocating losses to nodes it is understandable to identify dissimilarities. Moreover, this version of the method is applicable to radial distribution network with neglected influence of line shunt susceptances. The whole procedure is illustrated with a simple numerical example and it is also applied to a bigger system. The MATLAB code is given as an open-source for further research.
Keywords: Distributed power generation, Network losses, Loss allocation, Power distribution, Current tracing